Diagnostika cystické fibrózy u dospělých - Fila, Libor; Grandcourtová, Alžběta; Bartáková, Lucie Valentová; Antušová, Zuzana; Pokojová, Eva; Herout, Vladimír; Jakubec, Petr; Bittenglová, Radka; Marel, Miloslav (Vnitrni lekarstvi, 2016)
INTRODUCTION: There is an increasing number of cystic fibrosis (CF) patients with the diagnosis established in adulthood worldwide. AIM: To give an overview of our experience with the diagnostics of CF in adulthood in the Czech Republic. METHODS: CF patients with the diagnosis determined at the age 18 years during 2000-2014 period were selected from the Czech Registry of CF (www.cfregistr.cz). Demographic and clinical data were reported from medi-cal records at the time of diagnosis and as of 31st December 2014. Only those with two CF causing mutation or with one CF causing mutation together with sweat chloride concentration > 60 mmol/l were included in the study. The clinical presentation was compared with a control group consisting of homozygous F508del patients with the diagnosis established in childhood. RESULTS: 23 patients (16 men and 7 women) with the diagnosis determined at a mean age of 32.9 ± 8.5 years were included in the study. Presenting symptoms included bronchiectasis and/or haemoptysis in 12 cases, obstructive azoospermia in 7 cases and recurrent pancreatitis in 4 cases. When compared with the control group, the patients had higher age (38.6 ± 8.3 vs. 28.3 ± 4.7 years; p < 0.001), a lower concentration of sweat chloride (62 ± 23 vs. 90 ± 12 mmol/l; p < 0.001), less frequent airway infections with Pseudomonas aeruginosa and/or Burkholderia cepacia complex (4 vs. 12; p = 0.029), bronchiectasis (14 vs. 23; p = 0.001), exocrine pancreatic insufficiency (1 vs. 23; p < 0.001) and therapy with insulin (1 vs. 9; p = 0.01); on the contrary, pancreatitis was more frequent (6 vs. 0; p = 0.022). CONCLUSION: Diagnosis of CF in adults should be considered in those with corresponding symptoms in respiratory, digestive and reproductive tract. Clinical presentation differs from classical CF in many parameters. KEY WORDS: adults - cystic fibrosis - diagnostics.
Keywords: mutace; dospělí; Bronchiectasis; Pancreatitis, Chronic; Hemoptysis; Female; exokrinní pankreatická insuficience; Adult; ženské pohlaví; hemoptýza; Registries; cystická fibróza; lidé; azoospermie; Mutation; Azoospermia; bronchiektazie; Male; Czech Republic; Cystic Fibrosis; chronická pankreatitida; Česká republika; Exocrine Pancreatic Insufficiency; registrace; mužské pohlaví; Humans